Anisotropic Absorption Measurements Reveal Protein Dynamical Transition in Intramolecular Vibrations - Xu, M. Y.; Niessen, K.; Michki, N.; Deng, Y. T.; Snell, E.; Markelz, A. G. (2016 41st International Conference on Infrared, Millimeter, and Terahertz Waves, 2016)
Modeling has predicted that intramolecular structural vibrations enables proteins to access functionally important structural change. We show that the vibrational density of states and the isotropic absorption in the terahertz range are only weakly dependent on the protein functional state for several bench marking proteins. At the same time the direction of motions changes dramatically with functional state and with a resulting impact on the anisotropic absorption. Our anisotropic THz microscopy (ATM) measurements confirm this sensitivity. Here we apply the technique to the question of whether the protein dynamical transition (DT) is important to protein function. We find a strong anisotropic resonance at 70 cm(-1) rapidly increases in strength at temperatures above the DT. As these intramolecular vibrations enable protein structure to change conformation, the results suggest function will cease below DT for those proteins that require large scale conformational change.
ISI Document Delivery No.: BG7KC Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K., 2015, BIOPHYSICAL REV PETHIG R, 1995, PROTEIN SOLVENT INTE, P265 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Xu, Mengyang Niessen, Katherine Michki, Nigel Deng, Yanting Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 41st International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 25-30, 2016 Copenhagen, DENMARK DTU, IEEE, QMC Instruments, Danish Ctr Laser Infrastructure, DTU Fotonik, Dept Photon Engn, ARL, Carl Sberg Fdn, AF Off Sci Res, Tech Univ Denmark, IEEE Microwave Theory & Tech Soc, Azpect Photon, Ekspla, Hubner HF Syst Engn, I2S, Laser Quantum, Menlo Syst, Neaspec, Springer, TeraView, Virginia Diodes Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027